2022
DOI: 10.1136/archdischild-2022-323882
|View full text |Cite
|
Sign up to set email alerts
|

Short-term pulmonary and systemic effects of hydrocortisone initiated 7–14 days after birth in ventilated very preterm infants: a secondary analysis of a randomised controlled trial

Abstract: ObjectiveObservational studies in preterm infants suggest that systemic hydrocortisone improves pulmonary condition but may also lead to systemic adverse effects. We report the short-term pulmonary and systemic effects of hydrocortisone initiated in the second week.DesignRandomised placebo-controlled trial.SettingDutch and Belgian neonatal intensive care units.PatientsInfants born <30 weeks’ gestation and/or birth weight <1250 g, and ventilator dependent in the second week of life.InterventionInfants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…After a manual search of the reference list of the systematic reviews and meta-analyses analyzed in the previous stages, we added 28 RCTs, and 39 RCTs were analyzed in the final step of this systematic review ( Figure 1 ). Data extracted are summarized in Tables 1 – 6 ( 16 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After a manual search of the reference list of the systematic reviews and meta-analyses analyzed in the previous stages, we added 28 RCTs, and 39 RCTs were analyzed in the final step of this systematic review ( Figure 1 ). Data extracted are summarized in Tables 1 – 6 ( 16 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…A graphical representation of the percentage of the studies evaluating the outcomes of interest for this study is shown in Figure 2 ( 16 54 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations